Competitiveness implications for Ireland of EU enlargement - Frank G. Barry; Aoife Hannan; Colm Kearney (University College Dublin, Department of Economics, 2002)
Ten states, primarily from Central and Eastern Europe, are likely to be admitted to the EU within the next few years. The present paper assesses the competitiveness implications of this enlargement for Ireland. Four specific topics are considered: the trade effects, the implications for Irelands ability to attract FDI, the likely levels of immigration from Central and Eastern Europe and its consequences, and the budgetary implications for the Irish Exchequer.
hdl:10197/1326
Keywords: 330; EU-Erweiterung; Wirkungsanalyse; Internationaler Wettbewerb; Irland